2020
DOI: 10.1038/s41421-020-00210-9
|View full text |Cite
|
Sign up to set email alerts
|

Broad host range of SARS-CoV-2 and the molecular basis for SARS-CoV-2 binding to cat ACE2

Abstract: Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), the causative agent of the recent pandemic COVID-19, is reported to have originated from bats, with its intermediate host unknown to date. Here, we screened 26 animal counterparts of the human ACE2 (hACE2), the receptor for SARS-CoV-2 and SARS-CoV, and found that the ACE2s from various species, including pets, domestic animals and multiple wild animals, could bind to SARS-CoV-2 receptor binding domain (RBD) and facilitate the transduction of SARS-Co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

22
184
1
5

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 161 publications
(212 citation statements)
references
References 49 publications
(59 reference statements)
22
184
1
5
Order By: Relevance
“…Guo et al ( 30 ) reported that ACE2 genes showed high polymorphism among the R. sinicus populations, and R. sinicus ACE2 variants possessed different susceptibility to SARS-related-CoV infection. In the present study, together with the results from our previous work, our data showed that R. sinicus ACE2 could not bind to SARS-CoV-2 RBD ( 34 ). Zhao and colleagues ( 15 ) also reported R. sinicus ACE2 could not bind to SARS-CoV-2 RBD, although another report showed positive binding between R. sinicus ACE2 and SARS-CoV-2 RBD ( 13 ).…”
Section: Discussionsupporting
confidence: 82%
“…Guo et al ( 30 ) reported that ACE2 genes showed high polymorphism among the R. sinicus populations, and R. sinicus ACE2 variants possessed different susceptibility to SARS-related-CoV infection. In the present study, together with the results from our previous work, our data showed that R. sinicus ACE2 could not bind to SARS-CoV-2 RBD ( 34 ). Zhao and colleagues ( 15 ) also reported R. sinicus ACE2 could not bind to SARS-CoV-2 RBD, although another report showed positive binding between R. sinicus ACE2 and SARS-CoV-2 RBD ( 13 ).…”
Section: Discussionsupporting
confidence: 82%
“…As a consequence, a diverse range of vertebrates can be potentially infected by SARS-CoV-2 via their ACE2 receptors. This assumption is supported by the findings of ACE2 receptors in over 400 vertebrate species including both domestic and wild animals (Damas et al 2020 ; Wu et al 2020 ). SARS-CoV-2 infections have been recently confirmed in mammals including cats, monkeys, ferrets and hamsters (Santini and Edwards 2020 ).…”
Section: Infectable Vertebratesmentioning
confidence: 72%
“…Lau et al ( 2020 ) further showed that the entire genome of SARS-CoV-2 is most closely related to the SARSr-Ra-BatCoV RaTG13 from an intermediate horseshoe bat, except for its receptor-binding domain which is closest to pangolin-SARSr-CoVs, suggesting that SARS-CoV-2 is a recombinant virus. Overall, these findings indicate the complex origin of SARS-CoV-2, where evolutionary recombination and strong purifying selection occurred between strains from distinct host species before it spilled over to humans (Li et al 2020 ; Wu et al 2020 ; Sallard et al 2020 ). The back-and-forth transmission between human and wild species, when it occurs, may further enhance the genetic diversity of the virus.…”
Section: Mutations and Gene Mayonnaise Of Sars-cov-2mentioning
confidence: 93%
See 2 more Smart Citations